-2(3x-5)+8=-6x+18

Simple and best practice solution for -2(3x-5)+8=-6x+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x-5)+8=-6x+18 equation:


Simplifying
-2(3x + -5) + 8 = -6x + 18

Reorder the terms:
-2(-5 + 3x) + 8 = -6x + 18
(-5 * -2 + 3x * -2) + 8 = -6x + 18
(10 + -6x) + 8 = -6x + 18

Reorder the terms:
10 + 8 + -6x = -6x + 18

Combine like terms: 10 + 8 = 18
18 + -6x = -6x + 18

Reorder the terms:
18 + -6x = 18 + -6x

Add '-18' to each side of the equation.
18 + -18 + -6x = 18 + -18 + -6x

Combine like terms: 18 + -18 = 0
0 + -6x = 18 + -18 + -6x
-6x = 18 + -18 + -6x

Combine like terms: 18 + -18 = 0
-6x = 0 + -6x
-6x = -6x

Add '6x' to each side of the equation.
-6x + 6x = -6x + 6x

Combine like terms: -6x + 6x = 0
0 = -6x + 6x

Combine like terms: -6x + 6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5+9x=100 | | 65.66*6.28= | | 3y(2x-5y)= | | .9(7x+6)=2.5-(x-3) | | 2c+5-84=3c+6 | | -16x-32=-14x+55 | | 14c+5-32=3c+6 | | 9x-4-7x-10=-8x-11+17x-3 | | Y=.20x+160 | | 14c+35-4=3c+6 | | 0.0m=20.0m+a(12s) | | 25x^2+18=98 | | (5d^2-2g^5)(3g^3-h+4d^2)=0 | | 2p(p)(p)(0+2)+(p+2)=0 | | x-3(-4+9x)=16 | | 8x+3x-9x=4+2 | | 1+-8x=81+2x | | (5d^2-2g^5)-(3g^3-h+4d^2)=0 | | .50x+0.25(30)=42.5 | | [3a+8]=[4a-4] | | sqrt(8n-5)-1=2 | | 64+79= | | 2x+3x+9=6x-16 | | x-12-27x=16 | | 2d-5=d-1 | | 3+8x=4x-1 | | 3+3n=-4+2n | | 0=20+a(12) | | -16.1(t*t)+40t=4 | | (3k-1)(3k-1)=(5k+3)(3k-8) | | 1.08x=30 | | 2+-7k=20+-k |

Equations solver categories